Paying in public: Peer effects, impression management, and willingness to pay on digital payment platforms - Emily A. Kiernan; Jakina Debnam Guzman (PLoS ONE, 2026)
How do the social features of payment forms shape willingness to pay (WTP)? We conduct a purchasing experiment during Covid-19 in which 261 U.S. undergraduates are randomly assigned a payment form in which to complete a real transaction – either via debit card, credit card, or via one of the payment visibility settings within Venmo . We then elicit both stated preferences and WTP for ten household items. We find that the previously documented digital payment premium only persists when transactions are either private or are visible to the public at-large. When transactions are visible only to participants’ friends, however, we find a large decrease in their WTP consistent with impression management when peers are frugal. We find that viewing others’ transactions increases the magnitude of this effect. Payment visibility matters for WTP, but causes no differences in stated preference. These findings highlight the importance of considering social features of payment forms in addition to more well-documented features such as convenience, transparency and pain of payment.